The Influence Of Brand Image and Brand Experience on Cosmetic Makeover Brand Loyalty in Bandar Lampung - Karla Aisyah Putri; Roslina Roslina (Journal Economy and Currency Study (JECS), 2023)
The Indonesian cosmetics business is expanding at an unprecedented rate. Since there are so many cosmetics manufacturers, rivalry is fierce within both the domestic and international markets. The Compas team found that Make Over's facial cosmetics sales and statistics on the market still lag behind the market leader, Maybelline. Furthermore, Make Over still needs to be included in the Top Brand Index category, as it is mentioned by the Top Brand Index for a number of cosmetic products for 2020-2022. Make Over Cosmetics' biggest challenge is the abundance of similar products on the market. Since there are so many cosmetics manufacturers, rivalry is fierce within both the domestic and international markets. The purpose of this research is to analyze the connection between consumers' perceptions of the Make Over brand and their allegiance to the company among Bandar Lampung residents. Descriptive and proof analysis methodology was used for this study. Both primary and secondary sources were used to compile the information for this research. One hundred respondents were chosen using a non-probability sampling technique called purposive sampling, and online surveys were distributed to them via Google Forms; the gathered data was analyzed using multiple linear regression. This research found that brand loyalty is positively and significantly impacted by brand image and brand experience factors. Consumers are more likely to remain dedicated to a brand if they have a favorable impression of it and have a positive interaction with it. Holding activities is one way that Make Over can boost Brand Image. Make Over should not compromise product quality in order to provide a satisfying business experience for customers.